Kandungan Antioksidan Daun Mahang Damar (Macaranga triloba (Bl.) Muell Arg.) - Pienyani Rosawanti; Dewi Sari Mulia; Syahrida Dian Ardhany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
In the year 2015, the plants that initially grow a lot of wild is increasing in popularity because many contested by the citizens. The reason is because the plant has an economic value. Based on the literature review it is known that apigenin, a flavonoid compound has been isolated from the ethyl acetate fraction of methanolic extract of Macaranga gigantia leaf. Compounds that have potential as antioxidants are generally compounds of flavonoids, phenolics, and alkaloids. Flavonoid and polyphenolic compounds are antioxidant, antidiabetic, anticancer, antiseptic, and anti-inflammatory, while alkaloids have antineoplastic properties that also inhibit the growth of cancer cells. Phenol content, antioxidant activity and antibacterial activity were also found in Macaranga gigantea, M. hosei, M. hypoleuca, M. kingii, M. pruinosa and M. triloba (Lim et.al., 2014). This leads to the notion that mahang leaves were obtained and collected from the Central Kalimantan region where this study carried out also contained similar content and activity. Determination of the value of antioxidant activity in this study using DPPH method performed on n-hexane extract ofmahang leaf obtained by maceration. N-hexane extract of mahang leaf have antioxidant activity, this can be seen from the preliminary TLC test results where the spots produced when sprayed with DPPH fluoresce when viewed at 366 nm uv. The average value of IC50n-hexane extract of mahang leaves was 141.3 ppm.